Haemato-Biochemical Studies on Chronic Gastritis in Dogs - Manzoor, Irtiqa; Soodan, Jasvinder Singh; Tikoo, Abha; Sharma, Ankur; Ahmed, Jafrin Ara (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
This study was aimed to estimate the haemato-biochemical alterations in dogs suffering from chronic gastritis presented to Teaching Veterinary Clinical Complex of Faculty of Veterinary Sciences, Jammu for one year. A total of 30 clinically affected dogs presented with a history of chronic vomiting were included in the study and 6 healthy dogs were kept as a control group. Based on etiological factors, the diseased animals were divided into five groups: G1 (Foreign body), G2 (Renal failure), G3 (Hepatic origin), G4 (Diabetic origin), and G5 (Pyometra origin) with six animals in each group. Blood sampling was done on the day of presentation for all the groups to estimate haemato-biochemical parameters. Haemograms of dogs revealed low Hb, PCV and TEC in chronic gastritis due to renal, hepatic, diabetic and pyometra origin, and a significant increase in chronic gastritis due to gastric foreign body. A neutrophilic leukocytosis was observed in the foreign body, hepatic, diabetic, and pyometra groups, and neutropenia in the renal failure group. The biochemical parameters revealed a varied picture of reduced total protein and albumin and elevated BUN in the renal, diabetic, and pyometra groups. Creatinine and glucose levels revealed a significant increase in the renal and diabetic groups, respectively.